Penelitian ini bertujuan untuk mengetahui pengaruh implementasi teknik Team Quiz terhadap hasil belajar IPA siswa kelas V SDN 132/IV Kota Jambi Tahun Ajaran 2018/2019. Jenis penelitian ini adalah eksperimen dengan rancangan penelitian Randomized Control Group Only Design, sampel penelitian ini adalah seluruh siswa kelas V SD Negeri 132/IV Kota Jambi yang berjumlah 62 orang siswa. Hasil penelitian menunjukkan bahwa implementasi pembelajaran menggunakan teknik Team Quiz berpengaruh nyata pada tara - Kurnianingsih, Qonitah; Nurhasanah, Ana; Hakim, Zerri Rahman (Jurnal PGSD, 2020)
The purpose of this research is to know and analyze the application of SAVI (Somatic, Auditory, Visual, Intellectual) learning approach to student’s critical thinking skills on social science subjects in elementary school. This research used quasi experiment method with Nonequivalent Control Group Design. Sampling technique of the research used purposive sampling technique. The sample chosen was VA students as the experimental class that received treatment SAVI learning approach and VB students as the control class that received conventional learning. Based on the result of differences two averages posttest hypothesis test showed -2,01 < 2,67 > 2,01 (-ttable < ttest > ttable), then H0 is refused and Ha is accepted. It shows that there are differences of critical thinking skills between students who received SAVI learning approach with students who received conventional learning. The result of right side posttest hypothesis test showed -1,68 < 2,67 > 1,68 (-ttable < ttest > ttable), then H0 is refused and Ha is accepted. It shows that the critical thinking skills between students who received SAVI learning approach is higher than students who received conventional learning. It shows that SAVI learning approach can improve student’s critical thinking skills on social science subjects.